Political Consumerism Among Students : Understanding Motivations and Attitudes - Němeček, Daniel; Martínez Pantoja, Yadira Ixchel; San José Iglesias, Rafael; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
This thesis explores political consumerism among students, investigating motivations driving their support or boycott of products based on ethics. Using a questionnaire at Prague University of Economics and Business, key findings revealed that students engage in political consumerism primarily due to personal ethics, societal or environmental change aspirations, and a desire to influence government policies. Human rights emerged as the most critical value. The study emphasizes the significant role of corporate reputation in shaping students' preferences. Positive company reputations correlated with increased support, while negative perceptions led to boycotts. Additionally, Corporate Social Responsibility (CSR) initiatives positively influenced corporate reputations, but authenticity in CSR efforts was crucial. While underscoring the practical and theoretical contributions to understanding political consumerism, the study acknowledges limitations, including sample size and potential biases. The research highlights the need for businesses to align with evolving consumer values for sustained success.
Vedoucí práce: Yadira Ixchel Martínez Pantoja
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses